Fault Tolerant Attitude Control for Flexible Satellite with Uncertainties and Actuator Saturation. (4th June 2013) - Meng, Qiang; Zhang, Tao; Li, Da-Chuan; Liang, Jie-Mei; Liu, Bo; Song, Jing-Yan
A novel fault tolerant control scheme, using model-based control and time delay control theories, is proposed for flexible satellites with uncertainties and actuator saturation and the stability condition of the scheme is analysed. The moment–of-inertia uncertainty, actuator faults uncertainty, space environment disturbances and the actuator saturation are analysed. The computable control torques, including the space environmental torques, reaction wheel dynamics and the known flexible appendage dynamics, are formulated using the model-based control. The unknown flexible satellite dynamics is estimated according to its one-step previous value and employed to update the control command; this greatly reduces the conservativeness and enhances the pointing accuracy. Numerical simulations under different conditions demonstrate the advantages of the novel proposed controller compared to the conventional PD controller and a simplified fault tolerant controller.